2020
DOI: 10.1016/j.jaci.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-associated risk for COVID-19 development

Abstract: The newly described severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for a pandemic (coronavirus disease 2019 [COVID-19]). It is now well established that certain comorbidities define high-risk patients. They include hypertension, diabetes, and coronary artery disease. In contrast, the context with bronchial asthma is controversial and shows marked regional differences. Because asthma is the most prevalent chronic inflammatory lung disease worldwide and SARS-CoV-2 primarily affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 87 publications
(69 reference statements)
3
96
1
7
Order By: Relevance
“…Further research is warranted to improve our current understanding of the type 2 immune response in COVID‐19 as it is targeted by biologicals in the treatment of asthma and atopic dermatitis 100,101 . In addition, deeper insight into phenotypes and endotypes of asthma might provide more understanding of the pathophysiology of COVID‐19 in asthma 102 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…Further research is warranted to improve our current understanding of the type 2 immune response in COVID‐19 as it is targeted by biologicals in the treatment of asthma and atopic dermatitis 100,101 . In addition, deeper insight into phenotypes and endotypes of asthma might provide more understanding of the pathophysiology of COVID‐19 in asthma 102 …”
Section: Comorbiditiesmentioning
confidence: 99%
“…It would therefore appear that exacerbation of asthma is not the primary determinant of a severe disease requiring hospitalization but rather suggests that asthmatics may experience asthma exacerbations following the SARS-CoV-2 infection. More recently, different risks associated with SARS-CoV-2 infection and the disease development, progression, and severity have been connected differently across Th2 vs. non-Th2 asthma endotypes [ 123 ].…”
Section: Interrelation Between Covid-19 and Disorders With Mixed Or Mmentioning
confidence: 99%
“…Our studies reveal that IL-13 stimulation of HBECs affects expression of many SARS-CoV (13)(14)(15)(16). We also found significant associations of many IL-13-induced SARS-CoV-2associated genes with type 2 inflammation in a large group of smokers with and without COPD, suggesting that the effects of IL-13 on SARS-CoV-2 risk may also be relevant in some individuals without asthma.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent studies have failed to find consistent evidence of increased risk of COVID-19 diagnosis, hospitalization, or mortality due to asthma (1,9,10), and some studies concluded that risk of acquiring and being hospitalized for COVID-19 are lower in those with asthma (10,11). Factors that might provide protection against COVID-19 in individuals with asthma (12)(13)(14)(15) include increased attention to limiting viral exposure, younger age, absence of co-morbidities, use of inhaled corticosteroids, and a variety of biological features of asthma, including chronic airway inflammation, mucus hypersecretion, and altered expression of SARS-CoV-2 receptor (12). However, direct evidence that these features alter SARS-CoV-2 infection has been lacking.…”
Section: Introductionmentioning
confidence: 99%